Effect of silver nitrate incorporation into heat polymerized acrylic resin on some mechanical properties - Ola Kh Al-Husayni; Nabeel A Hatoor (College of Dentistry/ University of Baghdad, 2014)
Background: Polymers are very rarely used in their form. These modifications are carried out in order to improve the properties of polymers.Recently silver have been used successfully as antimicrobial (medical and dental) biomaterials that can prevent caries and infection of implants Purposes: The aim of the present in vitro study is to evaluate the effect of addition of silver nitrate to acrylic resin in different concentrationsthrough several tests part of these are: The effect of this additive on impact strength, transverse strength, and tensile strength of AgNO3 - loaded resin, and to assess any effect of addition of silver nitrate on coloration of acrylic resin. Materials and methods: Different concentrations of silver nitrate (9.375, 15, 30, 60, 120, 150, 300, 600 and 900 ppm) were prepared from stock solution of 1000 ppm silver nitrate. The specimens were prepared in accordance with the manufacturer's instructions and the tested silver nitrate solution was added to the acrylic resin powder and monomer in a fixed volume (0.2ml). Controls devoid of silver nitrate were included. Results: Fourier transform infra-red confirmed that there was no chemical bond between the Poly methyl methacrylate and silver nitrate. There was insignificant increasing (P=0.05) in impact strength observed when compared with control group. In transverse strength test, significant reduction was show (P